Compositionally graded crystals as a revived approach for new crystal engineering for the exploration of novel functionalities. Issue 13 (1st March 2022) - Matsumoto, Yuji; Maruyama, Shingo; Kaminaga, Kenichi
Abstract : Nanoscale compositionally graded crystals have huge potential to allow the exploration of new functionalities through crystal lattice modulation. Abstract : The original concept of nanoscale compositionally graded crystals (NCGCs) dates back to the mid-1980s; here, it is presented as a revived approach for new crystal engineering. The NCGCs are expected to exhibit a variety of novel functionalities that originate from the nanoscale composition gradients artificially implemented within these crystals. In this review article, after looking back at some of the related epoch-making work, an overview of recent studies on bulk and thin-film NCGCs is provided, covering essential topics such as ferroelectricity, magnetism, photocatalysis, and batteries. The review will allow readers to understand the promise of the nanoscale composition gradients approach for the design of new crystalline materials.